Identification and characterization of long intergenic noncoding RNAs in bovine mammary glands - Tong, Chao (BMC Genomics, 2017)
BACKGROUND: Mammary glands of dairy cattle produce milk for the newborn offspring and for human consumption. Long intergenic noncoding RNAs (lincRNAs) play various functions in eukaryotic cells. However, types and roles of lincRNAs in bovine mammary glands are still poorly understood. RESULTS: Using computational methods, 886 unknown intergenic transcripts (UITs) were identified from five RNA-seq datasets from bovine mammary glands. Their non-coding potentials were predicted by using the combination of four software programs (CPAT, CNCI, CPC and hmmscan), with 184 lincRNAs identified. By comparison to the NONCODE2016 database and a domestic-animal long noncoding RNA database (ALDB), 112 novel lincRNAs were revealed in bovine mammary glands. Many lincRNAs were found to be located in quantitative trait loci (QTL). In particular, 36 lincRNAs were found in 172 milk related QTLs, whereas one lincRNA was within clinical mastitis QTL region. In addition, targeted genes for 10 lincRNAs with the highest fragments per kilobase of transcript per million fragments mapped (FPKM) were predicted by LncTar for forecasting potential biological functions of these lincRNAs. Further analyses indicate involvement of lincRNAs in several biological functions and different pathways. CONCLUSION: Our study has provided a panoramic view of lincRNAs in bovine mammary glands and suggested their involvement in many biological functions including susceptibility to clinical mastitis as well as milk quality and production. This integrative annotation of mammary gland lincRNAs broadens and deepens our understanding of bovine mammary gland biology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3858-4) contains supplementary material, which is available to authorized users.